PENERAPAN SISTEM PERTANIAN TERPADU DI DESA KARANG BANGUN, KABUPATEN SIMALUNGUN - Lamria Sidauruk; Ernitha Panjaitan; Lince Romauli Panataria; Patricius Sipayung (Universitas Methodist Indonesia, 2021)
Karang Bangun Village is one of the centers for lowland rice production in Simalungun Regency, North Sumatra. The area of rice fields reaches 70% of the village area with good technical irrigation. However, the application of technology in the management of lowland rice in this village is still very conventional, and the knowledge of farmers about the new technology does not yet exist so that production only reaches 6 tons/ha. The purpose of this community service activity is to transfer the rice cultivation technology which is effective in increasing yields. The technologies are the application of the System of Rice Intensification (S.R.I) method, processing of straw waste into Bokashi organic fertilizer which can increase soil fertility, recognition of the symptoms of plant nutrient deficiency, and the use of plants as natural pesticides. Through assistance to farmers using a participatory approach in community service activities, the transfer of technology can run smoothly so that the use of irrigation water can be efficient, efficiently in using inorganic fertilizers, the use of inorganic pesticides is reduced and the productivity of farmers' land can be increased and by itself will improve the welfare of farmer.